2017
DOI: 10.1007/s10750-017-3271-7
|View full text |Cite
|
Sign up to set email alerts
|

Chirocephalus sarpedonis sp. nov. (Branchiopoda, Anostraca, Chirocephalidae) from Turkey questions the monophyly of the traditional Chirocephalus species-groups

Abstract: Chirocephalus sarpedonis sp. nov. (Anostraca, Chirocephalidae), collected in a temporary pond in Lycia (Turkey), is described and its affinities with the other species of the genus are investigated based on both morphology and mtDNA cytochrome oxidase subunit I (COI) sequences. Male and female morphology suggests its major affinity with the species belonging to the bairdi-group although the morphological peculiarities of the species make it difficult to ascribe C. sarpedonis sp. nov. to any of the Chirocephalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Such integrative approaches often revealed previously obscured relationships among genera and families (Remigio & Hebert, 2000;Weekers et al, 2002) and at the intrageneric or intraspecific levels (e.g., Ketmaier et al, 2003;Reniers et al, 2013;Gandolfi et al, 2015). This is also demonstrated in two contributions in this volume: Cottarelli et al (2017), using mtDNA sequences and morphology to define a new Chirocephalus species collected in Turkey, questions the validity of the traditionally accepted species-groups within the genus, and; Kappas et al (2017) rejects the subspecific differentiation of eastern versus western Streptocephalus torvicornis (Waga, 1842) populations based on a morphological re-analysis of both adults and eggs and on mtDNA sequences.…”
Section: Systematics and Phylogenymentioning
confidence: 70%
“…Such integrative approaches often revealed previously obscured relationships among genera and families (Remigio & Hebert, 2000;Weekers et al, 2002) and at the intrageneric or intraspecific levels (e.g., Ketmaier et al, 2003;Reniers et al, 2013;Gandolfi et al, 2015). This is also demonstrated in two contributions in this volume: Cottarelli et al (2017), using mtDNA sequences and morphology to define a new Chirocephalus species collected in Turkey, questions the validity of the traditionally accepted species-groups within the genus, and; Kappas et al (2017) rejects the subspecific differentiation of eastern versus western Streptocephalus torvicornis (Waga, 1842) populations based on a morphological re-analysis of both adults and eggs and on mtDNA sequences.…”
Section: Systematics and Phylogenymentioning
confidence: 70%
“…Upon aligning our Cretan Chirocephalus sequences and those downloaded from GenBank, and having trimmed the tails of the sequences which were not present in all the individuals, we obtained a properly aligned 408 bp-long fragment of the mtDNA COI. BI and ML trees, rooted on Chirocephalus kerkyrensis Pesta, 1936 (a species belonging to the bairdi-species group of the genus Chirocephalus, see discussion in Cottarelli et al, 2017), showed a consistent topology at the major nodes (Fig. 2).…”
Section: Resultsmentioning
confidence: 95%
“…from sites GR084 and GR099 (Crete, Greece) were studied by amplifying and sequencing a fragment of the mitochondrial gene encoding for the cytochrome oxidase subunit I (COI), a molecular marker widely used in the molecular systematics and phylogeography of Chirocephalus (e.g. : Ketmaier et al, 2012;Reniers et al, 2013;Zarattini et al, 2013;Cottarelli et al, 2017). Comparative sequences belonging to other C. diaphanus s.l.…”
Section: Gsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the family Chirocephalidae, Chirocephalus salinus Daday, 1913 is widespread throughout the island (Mura 2006), whereas the congeneric C. diaphanus is to date only reported from a single temporary pond on Sant'Antioco island . Considering the unsettled taxonomy and nomenclature of the diaphanus-group within the genus Chirocephalus, and of the possible presence of cryptic species currently lumped under widely-used binomia (Reniers et al 2013;Cottarelli et al 2017;Marrone et al 2019a), a morphological and molecular characterization of Sardinian Chirocephalus populations and their comparison with topotypical specimens for the available Chirocephalus specific epithets is desirable.…”
Section: Anostracamentioning
confidence: 99%